Analisis Big Data Hukum Pariwisata Internasional Periode 2017-2023 - Arief Purnama Ajie; Andin Rusmini (PT. PENERBIT TIGA MUTIARA, 2023)
This study, conducted from 2017 to 2023, analyzes the relationship between international tourism and law using bibliometric methods on a dataset of 237 selected documents. The findings reveal a declining trend in annual dataset growth, with an average document age of approximately 2.93 years. The study delves into author collaboration, document types, and keyword usage. There was an average of 4,042 citations per document, reflecting the scholarly impact in the field. The dataset included 714 plus keywords and 738 author keywords, contributing to content analysis. Among the 570 unique authors, 87 were sole authors, while 99 documents were single-authored, and the average co-authorship was 2.47. Notably, there was no international co-authorship in the dataset. Document types encompassed articles, books, book chapters, conference papers, and more, with peak scientific production observed in 2020. Treemap and thematic map analysis visualize term distribution and research trends.